2010
DOI: 10.1590/s1516-05722010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Calagem e adubação orgânica na produção de biomassa e óleo essencial em Lippia citriodora (Kunth)

Abstract: RESUMO:O presente trabalho objetivou avaliar a calagem e adubação orgânica na produção de biomassa e óleo essencial em Lippia citriodora Kunth. O delineamento experimental utilizado constou de fatorial 7 x 2, sendo sete tratamentos (testemunha; adição de sulfato de Ca e Mg; calcário dolomítico; silicato de Ca e Mg; sulfato de Ca e Mg + esterco de curral; calcário dolomítico + esterco de curral; silicato de Ca e Mg + esterco de curral) e duas épocas de colheita, com quatro repetições, inteiramente casualizado (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…Being also different from the authors Oliveira Junior et al (2006); Calgaro et al (2007); Costa et al (2007) and Souza et al (2010) where the treatments were not significant in the production of Essential Oil with the use of soil pantic.…”
Section: Source: Authorscontrasting
confidence: 80%
See 1 more Smart Citation
“…Being also different from the authors Oliveira Junior et al (2006); Calgaro et al (2007); Costa et al (2007) and Souza et al (2010) where the treatments were not significant in the production of Essential Oil with the use of soil pantic.…”
Section: Source: Authorscontrasting
confidence: 80%
“…This result differs from the authors Mascarenhas et al (1990); Mascarenhas et al (1996); Faria et al (2003); Silva et al (2007); Ayres and Alfaia (2007) and Benedetti et al (2009), because the behavior was partially the opposite to that observed. As for the authors Oliveira Junior et al (2006); Calgaro et al (2007); Costa et al (2007) and Souza et al (2010) that had as results, average stake of treatments with soil cathem not significant in the production of Essential Oil. Where: no lime (SC) addition; Correction of base saturation to 20% (S20); Correction of base saturation to 40% (S40); Correction of base saturation to 60% (S60) and Correction of base saturation to 80% (S80).…”
Section: Source: Authorsmentioning
confidence: 73%
“…O mesmo também foi constatado por Souza et al (2010), ao trabalharem adubação orgânica em plantas de Lippia citriodora Kunth. Esses resultados podem estar ligados ao fornecimento de nutrientes por parte dos adubos orgânicos para os vegetais, já que, a maior parte destes se caracteriza pela presença de grandes quantidades de nutrientes, em especial, de macronutrientes.…”
Section: Resultsunclassified
“…Souza et al (2010) FIGURE 5. Effect of four levels of organic fertilization (0, 3, 6 and 9 kg m -2 ) on production of fresch and dry weight (g), essential oil, and essential oil/dry weight by Lippia sidoides Cham.…”
Section: Resultsmentioning
confidence: 99%